2021
DOI: 10.1111/nph.17434
|View full text |Cite
|
Sign up to set email alerts
|

Climate warming dominates over plant genotype in shaping the seasonal trajectory of foliar fungal communities on oak

Abstract: Leaves interact with a wealth of microorganisms. Among these, fungi are highly diverse and are known to contribute to plant health, leaf senescence and early decomposition. However, patterns and drivers of the seasonal dynamics of foliar fungal communities are poorly understood.We used a multifactorial experiment to investigate the influence of warming and tree genotype on the foliar fungal community on the pedunculate oak Quercus robur across one growing season.Fungal species richness increased, evenness tend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 115 publications
(154 reference statements)
3
37
1
Order By: Relevance
“…With greenhouse gas emissions, some species will migrate to high latitude or high elevation, while other species maintained the current location by changing physiologically or phenologically ( Zhang et al, 2018 ; Faticov et al, 2021 ). Our prediction showed that the shift of F. cirrhosa from current altitude to higher altitude would become gradually more significant.…”
Section: Discussionmentioning
confidence: 99%
“…With greenhouse gas emissions, some species will migrate to high latitude or high elevation, while other species maintained the current location by changing physiologically or phenologically ( Zhang et al, 2018 ; Faticov et al, 2021 ). Our prediction showed that the shift of F. cirrhosa from current altitude to higher altitude would become gradually more significant.…”
Section: Discussionmentioning
confidence: 99%
“…It was also followed by an increase in pathogen occurrence. [ 26 ] Grasslands A decreased ‘drift’ was observed over time, which enhances homogeneous selection that is primarily imposed on Bacillales. [ 27 ] Soil leaf litter layer A short-term adaptation and altered diversity were observed.…”
Section: Resultsmentioning
confidence: 99%
“…In the frame of the SPRUCE macrocosm experiment, Carell et al [ 25 ] deciphered that a microbiome shift in Sphagnum was connected with a decreased diversity of bacteria and diazotrophs as well as a reduced nitrogen fixation rate. Another warming experiment that was carried out under controlled conditions provided clear evidence that the diversity of oak-inhabiting fungi is reduced [ 26 ]. Microbiota shifts and fast selection processes were described in various studies, where the taxonomy of selected species showed variations, but also showed a clear tendency towards pathogens and spore-forming organisms [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…The foliar endophytic fungal community in Cirsium arvense could be associated with the soil nutrients and arbuscular mycorrhizal (AM) colonization ( Eschen et al, 2010 ), and the latter would be further affected by root exudates, such as methyl salicylic acid and acibenzolar- S -methyl ( Mannaa et al, 2020 ). Furthermore, climate change, such as warming, would decrease fungal species richness and change foliar fungal community composition, especially at the end of the growing season ( Faticov et al, 2021 ). In the case of elevated atmospheric carbon dioxide, the growth of trees would also lead to the changes in the composition of microbial communities that colonize the fallen leaves ( Kelly et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Microbial community networks can provide a mechanistic association between species in a specific environment and information on the dynamics of community structure as a function of time or other external variables ( Cardona et al, 2016 ). For example, climate change, such as warming, can significantly increase network complexity, including network size, connectivity, and number of keystone species ( Faticov et al, 2021 ), whereas elevated CO 2 can increase modularity and hierarchy ( Zhou et al, 2010 ). The community assembly of plant-associated microbes may have some differences, such as the rhizosphere microbial networks.…”
Section: Introductionmentioning
confidence: 99%